Bond strengths of composite resins used for the attachment of bonded retainers/ Saraswathy D Sinniah ... [et al.] - Sinniah, Saraswathy D; Jones, Steven P; Georgiou, George; Cunningham, Susan J; Petrie, Aviva (Faculty of Dentistry, 2016)
Objectives: To compare the bond strengths and survival of flowable and non-flowable composite resins used with bonded retainers. Setting: Department of Orthodontics, UCL Eastman Dental Institute, United Kingdom. Methods: Flowable composite resins (TransbondTM Supreme LV, StarFlowTM and Tetric EvoFlow®) and non-flowable control resin (TransbondTM LR) were made into cylinders prior to bonding to hydoxyapatite discs. They were then mounted into jigs and tested in the InstronTM Universal Testing Machine in both shear and tensile modes. Results: The highest mean shear bond strength was seen with StarFlowTM (14.09 MPa), which was significantly higher than both TransbondTM LR (9.48 MPa) and TransbondTM Supreme LV (8.20 MPa). The mean shear bond strength of Tetric EvoFlow®(11.86 MPa) was also significantly higher than TransbondTM Supreme LV. The highest mean tensile bond strength was seen with Tetric EvoFlow®(2.14 MPa), which was significantly higher than TransbondTM LR (1.15 MPa) and TransbondTM Supreme LV (0.61 MPa) but not significantly different to StarFlowTM (1.47 MPa). For shear loading, StarFlowTM had the highest 50th percentile survival estimate at 15.10 MPa, followed by Tetric EvoFlow®(13.00 MPa) and TransbondTM Supreme LV (7.50 MPa). TransbondTM LR had a 50th percentile estimate at 9.00 MPa. For tensile loading, Tetric EvoFlow®had the highest 50th percentile survival estimate at 2.50 MPa, followed by StarFlowTM (1.30 MPa) and TransbondTM Supreme LV (0.50 MPa). TransbondTM LR had a 50th percentile estimate at 1.00 MPa. Conclusions: Mean shear bond strengths for all of the resins were significantly higher than the mean tensile bond strengths. StarFlowTM and Tetric EvoFlow®could potentially be suitable clinical alternatives to TransbondTM LR due to its low viscosity flow characteristics and adequate shear and tensile bond strengths.